Kazimierz Brandys i prawda pojedyncza - Wołk, Marcin (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2018)
KAZIMIERZ BRANDYS AND SINGULAR TRUTH The article offers a comprehensive overview of Kazimierz Brandys’s works, exploring them in a personal perspective as the writer’s struggle with the experience of imposed and undesirable otherness. It analyzes elements of the writer’s autobiography and biography as well as references to his Jewish origin (increasingly pronounced since the late 1960s), the play with his family name, plot structures interweaving Polish and Jewish motifs, the themes of family and lineage, his characters’ recurring experience of exclusion or rejection, his predilection for subjective forms, such as the journal or the letter, and his, often expressed, sense of being unjustly assessed by critics. The author of the article approaches Brandys’s writing in terms of constant defiance of the tyranny of external circumstances, accompanied by a strong conviction of its futility. KAZIMIERZ BRANDYS ET LA VÉRITÉ INDIVIDUELLE L’article propose un regard synthétique sur l’œuvre de Kazimierz Brandys, il la relit d’après une perspective personnelle comme le combat de l’auteur avec l’expérience d’une altérité non-désirée et imposée. L’article analyse les thèmes autobiographiques et biographiques, les mentions de ses origines juives par l’écrivain (de plus en plus fréquentes à partir des années 60), les jeux auxquels ce dernier se livre avec son nom propre, les constructions fabulaires mêlant des trames polonaises et juives, le motif de la famille et de la généalogie, l’expérience répétée chez ses protagonistes de l’exclusion et du rejet, l’affection pour les formes subjectives d’expression comme le journal intime et la lettre, ainsi que le sentiment maintes fois exprimé par l’auteur de l’injustice de ses évaluations critiques. L’auteur de l’article interprète l’écriture de Brandys comme l’expression conséquente d’une révolte contre la tyrannie de circonstances imposées, matinée de la conviction que cette révolte est vaine.